Emerging natural fiber-reinforced cement materials and technology for 3D concrete printing: a review - Mohd Zainuri, Mohamad Izwan Saifudin; Wahab, Md Saidin; Hj Ibrahim, Mustaffa; Marwah @ Omar, Omar Mohd Faizan; Sa'ude, Nasuha (UTHM Publishing, 2020)
Additive Manufacturing (AM) technology has been widely used in various industries like automotive, manufacturing and construction. The application of AM technology in the construction industry is a chance of significant improvement and advancement for constructing processes. AM is consist of creating layer by layer of slices to print 3-dimensional (3D) construction parts. In this regard, along with the technology and process of 3D printing in construction; many researchers worked on different materials included natural fibre reinforced cement for the 3D construction advancement. On such, the review has been done for 3D printing technology, process, latest machinery for construction, the construction flow process and emerging materials for 3D construction. For this, the most recent and critical research work since last 8-years was highlighted and argued. Different research articles and numerous latest reports from web blogs are used for furnishing this review work. Based on the review, few research gaps are discovered. Finally, the use of 3D printing in the construction industry depends on the accuracy of the printing job. Not only that, the availability of printing materials and the cost of the printing process and the time taken to print also become the factors in the technology revolution in the construction industry.